(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A kind of photosynthetic bacteria known as blue-green algae (BGA) can fix atmospheric nitrogen and are crucial for increasing soil fertility. Increased nitrogen, phosphorus, and other important nutrient availability to plants due to the presence of BGA in the soil can result in better plant development and greater yields. Despite the fact that cyanobacteria and microalgae are common in soil, little attention has been given to their potential. The indiscriminate application of several pesticides to increase agricultural output has major side effects, including structural instability, the buildup of hazardous pollutants, and an imbalance in the ecology of the soil, plants, and microbiota. The purpose of the present critical review is to highlight the significance of this particular group of microorganisms in terms of maintaining soil fertility and soil health. Beneficial soil ecological applications of these two groups in enhancing plant growth, establishing interrelationships among other microbes, and detoxifying chemical pollutants have been demonstrated. The advantages and disadvantages of various such cutting-edge methodologies for utilizing the biotechnological potential of these photosynthetic microorganisms for sustainable agriculture were also covered. Recombinant technology involving genomic integration favors the development of useful traits in microalgae and cyanobacteria for their potential application in improving soil fertility and health. We also talk about potential future research paths as well as the difficulties that come with using BGA in agriculture.